Who counts? the mathematics of life and death after genocide - Nelson, Diane M., 1963- (Duke University Press, 2015)
In Who Counts? Diane M. Nelson presents a complex reading of mathematics and the contested and myriad ways it is used by the Guatemalan state to marginalize indigenous populations as well as its use by indigenous peoples to critique systemic inequalities.